Early childhood weight gain: Latent patterns and body composition outcomes. Issue 5 (7th May 2021) - Norris, Tom; Mansukoski, Liina; Gilthorpe, Mark S.; Hamer, Mark; Hardy, Rebecca; Howe, Laura D.; Li, Leah; Ong, Ken K.; Ploubidis, George B.; Viner, Russell M.; Johnson, William
Abstract: Background: Despite early childhood weight gain being a key indicator of obesity risk, we do not have a good understanding of the different patterns that exist. Objectives: To identify and characterise distinct groups of children displaying similar early‐life weight trajectories. Methods: A growth mixture model captured heterogeneity in weight trajectories between 0 and 60 months in 1390 children in the Avon Longitudinal Study of Parents and Children. Differences between the classes in characteristics and body size/composition at 9 years were investigated. Results: The best model had five classes. The "Normal" (45%) and "Normal after initial catch‐down" (24%) classes were close to the 50th centile of a growth standard between 24 and 60 months. The "High‐decreasing" (21%) and "Stable‐high" (7%) classes peaked at the 91st centile at 12‐18 months, but while the former declined to the 75th centile and comprised constitutionally big children, the latter did not. The "Rapidly increasing" (3%) class gained weight from below the 50th centile at 4 months to above the 91st centile at 60 months. By 9 years, their mean body mass index (BMI) placed them at the 98th centile. This class was characterised by the highest maternal BMI; highest parity; highest levels of gestational hypertension and diabetes; and the lowest socio‐economic position. At 9 years, the "Rapidly increasing" class was estimated to have 68.2% (95% confidence interval [CI] 48.3, 88.1) more fat mass than the "Normal" class, but only 14.0% (95% CI 9.1, 18.9) more lean mass. Conclusions: Criteria used in growth monitoring practice are unlikely to consistently distinguish between the different patterns of weight gain reported here.